Factors affecting utilization of mental health services from Primary Health Care (PHC) facilities of western hilly district of Nepal. - Gaurav Devkota; Puspa Basnet; Bijay Thapa; Madhusudan Subedi (PLoS ONE)
Aim To explore the factors affecting mental health service utilization from Primary Health Care facilities of Arghakhanchi district, a western hilly district of Nepal. Background Mental health service utilization has many facilitating and hindering factors present at different socio-ecological levels. Stigma and lack of awareness in the community have been identified as the major barriers for mental health service demand and access worldwide. Methods A cross-sectional qualitative study was conducted in Arghakhanchi district of Nepal in July-August 2019 that collected information through face-to-face In-depth and Key Informant Interviews of three categories of participants selected judgmentally. Thirty-two purposively selected participants from the three categories were interviewed using validated interview guidelines. Thematic analysis was performed using RQDA package for EZR software. Validation of translated transcripts, member checking and inter-coder percent agreement were performed to maintain rigor in the study. Results Mental health stigma and inadequate awareness were identified as major factors that caused barriers for mental health service utilization at community level. They also influenced different factors at other socio-ecological levels to act as barriers. Awareness in community along with accessibility and availability of comprehensive mental health services were recommended by the participants for increasing service utilization from Primary Health Care facilities. Conclusion Individual, family and community awareness could help reduce and/or eliminate mental health stigma. Accessibility of health facilities and availability of comprehensive mental health services in Primary Health Care facilities could help increase service utilization from those facilities.